The People’s Republic of China’s Strategy in The Three Sea Domain: The East China Sea, South China Sea, Indian Ocean, and The US’s Struggle for Presence in This Region - Murat Kağan Kozanhan (Siyasal: Journal of Political Sciences)
China is consolidating its presence in the region through strategies it is implementing in the East China Sea, the South China Sea and the Indian Ocean. These strategies ensure the distant defense of its homeland and challenge the United States’ struggle for dominance in these three maritime areas. China is implementing the “Active Strategic Counter Attack Against Exterior Lines (ASCEL) Concept” in the East China Sea, which is the first region of these maritime areas. Second, China is developing its retaliatory capabilities in the South China Sea. Third, in the Indian Ocean; China is investing heavily in military technology and in the ports of some of the states with which it has close relations in the region to use them as a support area. In this study, qualitative research techniques are used to analyze China’s activities in the East China Sea, South China Sea and Indian Ocean where China has implemented a three-region maritime strategy. This study aims to evaluate the PRC’s practices in the Indo-Pacific Region against the United States’ efforts to exist in the region and the policies of the two countries in the three maritime areas where both countries confront each other in a way that could lead to a hot conflict by utilizing document analysis, content analysis and discourse analysis methods.